Social Welfare Model of Rural Development - Badal, Bharat Prasad (Nepalese Journal of Development and Rural Studies, 2017)
After analyzing the balanced growth unbalanced growth, unlimited supply of laborer, transformation of traditional agriculture and social choice theories as well as Gandhian model of rural development, US market model economy, Chinese socialist’s economy, Korean model of rural development (Saemual Undong), mix welfare model of Sweden, this paper emphasizes that people’s participation is inevitable to achieve desired development goals. However, all these doctrines, theories or model have identified active participation of the people in development process but still those doctrines are silent about how to emancipate and mobilize people. Here is why, this paper has designed and developed social welfare model of Rural Development (SWMRD) based on Sen’s social choice theory, Gandhian model of rural development and doctrine of factors of production of economics. According to the model people have to make plan of their resources for sustainable economic return and its implementation. Government has to assure freedom, human right, motivation and protection. Hence, SWMRD model will be applicable on development studies and useful to development policy makers. Nepalese Journal of Development and Rural Studies Vol. 14 (Joint issue) (1&2), 2017, Page: 1-11